Environmentally friendly export business strategy: Its determinants and effects on competitive advantage and performance - Leonidou, Leonidas C.; Fotiadis, Thomas A.; Christodoulides, Paul; Spyropoulou, Stavroula; Katsikeas, Constantine S. (My University, 2015)
With the exponential growth of problems related to the natural environment, exporters are increasingly confronted with ecological challenges in their international operations. We present a study of exporting manufacturers that examines the external and internal determinants of green export business strategy and its effects on export competitive advantage and performance. Our findings confirm the instrumental role of both external forces (i.e., foreign environmental public concern and competitive intensity) and internal factors (i.e., top management green sensitivity and organizational green culture) in crafting an environmentally friendly export business strategy. Such a strategy was more prevalent among larger firms and more experienced exporters, as well as among firms producing industrial goods, having a high technological intensity, and exporting to developed countries. In addition, this strategy positively affected firms' export product differentiation advantage but had no effect on export cost leadership advantage. Export product differentiation advantage was positively associated with both export market performance and export financial performance. However, no such link with these performance dimensions appeared for export cost leadership advantage.
Keywords: Competitive advantage; Environmentally friendly business strategy; Export performance; Exporting